Effect of HAp on Characterization of MgZn-xHAp Biocomposites - Henni Sitompul; Yohanes Edi Gunanto; Maya Puspitasari Izaak (Jurnal Fisika dan Aplikasinya, 2021)
Research on Mg as biodegradable materials in orthopedics has been carry out intensively in the 17 years. Various studies conducted to produce material that is superior in mechanical properties and corrosion resistance. One of the developments carry out is to make Mg-based composite. This study aims to see the effect of HAp on Mg6ZnHAp composites. The biocomposites were synthesized by mixing the HAp powder on the Mg6Zn powder mixture with the composition of 5%, 7% and 9% using ball milling for 30 minutes. The material is sintered at 350 oC and held for one hour. Biocomposites were characterized by SEM/EDS, X-ray diffraction (XRD) and Potentiostat. The SEM/EDS results showed that the larger the HAp composition resulted in the smaller grain size. The crystallite size of the material decreases with increasing HAp composition in the material. The presence of HAp in the material also affects the corrosion rate. The greater HAp composition in the material will result in better corrosion resistance.